2014
DOI: 10.1111/hiv.12175
|View full text |Cite
|
Sign up to set email alerts
|

Factors responsible for incomplete linkage to care after HIV diagnosis: preliminary results from the Test and Keep in Care (TAK) project

Abstract: ObjectivesLinkage to care after HIV diagnosis remains underinvestigated in Europe, yet delays in linkage to care are an important obstacle to controlling the HIV epidemic. The Test and Keep in Care (TAK) project aims to determine the prevalence of HIV-positive persons who are lost or late to care and factors associated with this. MethodsData from community-based voluntary counselling and testing that occurred in 2010-2011 were linked with data from HIV clinics using unique test numbers. Persons not registered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…It should be noted that, in Poland, HIV testing services are largely provided in community‐based voluntary counselling and testing (VCT) facilities (free of charge) and through parallel testing via private laboratories (costing 10–20 euro/test). VCT facilities provide anonymous testing that is available to all adults, including migrants, regardless of medical insurance; however, it has been shown that linkage to care may be as low as 62.1%, with barriers to care entry being bi‐ or heterosexual orientation, lower level of education, young age and inconsistent condom use . This implies that the fear of stigma, discrimination and disclosure of sexual orientation may still play a role in delayed testing and therefore care entry.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, in Poland, HIV testing services are largely provided in community‐based voluntary counselling and testing (VCT) facilities (free of charge) and through parallel testing via private laboratories (costing 10–20 euro/test). VCT facilities provide anonymous testing that is available to all adults, including migrants, regardless of medical insurance; however, it has been shown that linkage to care may be as low as 62.1%, with barriers to care entry being bi‐ or heterosexual orientation, lower level of education, young age and inconsistent condom use . This implies that the fear of stigma, discrimination and disclosure of sexual orientation may still play a role in delayed testing and therefore care entry.…”
Section: Discussionmentioning
confidence: 99%
“…This happened despite universal adoption of proactive linkage procedures by Polish VCT centers. 13 Such high number of persons LTC necessitates rapid improvement so that neither funds nor lives are lost despite timely diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the newest guidelines of the PTN AIDS and EACS, each patient with the confirmed HIV infection and the readiness to take up treatment should begin it without undue delay [24,26]. The percentage of the persons receiving effective therapy and persons with its full effectiveness in Poland is high, yet the percentage of the persons who seek medical care after the HIV infection diagnosis remains unsatisfying [27,28].…”
Section: Discussionmentioning
confidence: 99%